2020
DOI: 10.2967/jnumed.120.253062
|View full text |Cite
|
Sign up to set email alerts
|

Impact of 68Ga-FAPI PET/CT Imaging on the Therapeutic Management of Primary and Recurrent Pancreatic Ductal Adenocarcinomas

Abstract: German Cancer Consortium (DKTK), partner site Heidelberg, Germany.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
206
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 139 publications
(227 citation statements)
references
References 34 publications
(30 reference statements)
18
206
2
1
Order By: Relevance
“…]Ga-DOTA-FAPI-04 PET/CT had a higher detection rate in metastatic LNs, liver, and peritoneum metastases, which was in consistent with the nding of a previous study [17]. The favorable imaging contrast de nitely makes [ 68 Ga]Ga-DOTA-FAPI-04 a tracer with high sensitivity for the diagnosis of pancreatic cancer.…”
Section: Clinical Characteristics Of the Patientssupporting
confidence: 88%
See 2 more Smart Citations
“…]Ga-DOTA-FAPI-04 PET/CT had a higher detection rate in metastatic LNs, liver, and peritoneum metastases, which was in consistent with the nding of a previous study [17]. The favorable imaging contrast de nitely makes [ 68 Ga]Ga-DOTA-FAPI-04 a tracer with high sensitivity for the diagnosis of pancreatic cancer.…”
Section: Clinical Characteristics Of the Patientssupporting
confidence: 88%
“…And most of them were with diffuse uptake in the body and tail of pancreas. Previous studies have also revealed the similar performance and tumors showed higher average SUV max than pancreatitis [17,23]. However, the SUV max of the tumors and non-tumor pancreas was similar in our study.…”
Section: Clinical Characteristics Of the Patientssupporting
confidence: 69%
See 1 more Smart Citation
“…Recently, significant FAPI avidity was demonstrated in pancreatic cancer patients [ 13 ]. Furthermore, FAPI-PET/CT imaging influences tumor staging and oncological treatment when compared to contrast-enhanced CT scans [ 15 ]. Therefore, we hypothesized that FAPI-PET/CT imaging could improve GTV definition in locally recurrent pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…CAFs, especially in higher density are known to play an essential role in the development, progression, expansion and therapy resistance of PDACs [ 14 ]. Recently, Röhrich et al could demonstrate that FAPI-PET/CT imaging leads to significant changes in tumor staging compared to standard imaging [ 15 ]. In seven of the 19 analyzed patients, FAPI-PET/CT even influenced oncological treatment.…”
Section: Introductionmentioning
confidence: 99%